PENGARUH KUALITAS PRODUK, DESAIN PRODUK, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN TAS MEREK EXSPORT DI SURABAYA - Dinha, Niaza; Maduwinarti, Ayun; Pujianto, Agung (Jurnal Dinamika Administrasi Bisnis, 2020)
Abstrack The bussiness world is growing rapidly everyday. This situation make the enterpreneurs doing varrious efforts to create a superior product to make consumers buy their products. The entrepreneurs need the right strategy to create a product with a good quality and different with the products from their competitors. The aims of this research is to find out and analyze the influence of product quality, product design, and brand image on purcase decision of Exsport bag in Surabaya. The type of research used is quantitaive. The data was collected by quesionnare. The population in this research is consumers which have bought the Exsport bags in Surabaya. The sample that used is non probability sampling methods with purposive sampling technique, with a sample of 96 respondents. The data analysis methods used is multiple regression anaylsis, t test, adn F test.The result of this research shows that all the independent variabels that are product quality, product design, and brand image both partially and simultanously are having a positive and significanly on the dependent variable that is purcase decision. Keywords : Product Quality, Product Design, Brand Image, Purchase Decision